Complementary feeding hygienic practices and its associated factors among mothers of children aged 6–23 months old in Central Ethiopia, 2023 - Akiso, Denebo Ersulo; Laelago, Sinidu (Frontiers in Public Health, 2025)
BackgroundComplementary feeding is a critical period for child development and normal nutritional status, playing a vital role in the prevention of malnutrition and related health issues. However, poor hygiene practices during this phase can lead to foodborne diseases and inadequate nutrient intake.ObjectiveTo assess poor hygienic practice related to complementary feeding and associated factors among mothers of children aged 6–23 months in Lemo District, 2023.MethodsA community-based cross-sectional study was conducted from September to November 2023, utilizing a systematic sampling technique. A total of 402 mother–child pairs were randomly selected for participation. Data were collected using a pretested and structured questionnaire and then entered into Epi-Data version 4.6. The data were subsequently exported to SPSS version 26 for analysis. In the multivariable binary logistic regression analysis, variables with a p-value less than 0.05 were deemed to be statistically significant.ResultsThe prevalence of poor hygienic practices related to complementary feeding among mothers of children aged 6–23 months was found to be 65%. Factors significantly associated with poor hygienic practices of complementary feeding was the absence of a separate kitchen [AOR = 3.17, 95% CI: (1.32, 7.59)], lack of access to a protected source of drinking water [AOR = 8.17, 95% CI: (3.06, 18.7)], and lack of access to media [AOR = 2.12, 95% CI: (1.25, 3.6)].ConclusionThe study revealed a significant prevalence of inadequate hygienic practices in the context of complementary feeding among mothers. Factors that were identified as significant contributors to the observed poor hygienic practices includes the absence of separate kitchen, unprotected source of drinking water, and a lack of exposure to media.